Improvement of the Energy System of a Nepali Village Through Innovative Exploitation of Local Resources. (November 2016) - Benato, Alberto; Pezzuolo, Alex; Stoppato, Anna; Mirandola, Alberto; Pandey, Suraj
Abstract: Nepal is one of the less industrialized Countries and does not have fossil fuel reserves. In this scenario, a better exploitation of energy resources is a key factor to start improving the country's overall energy system. For these reasons, the aim of this work, which is the result of a collaboration between two research groups from different countries, is the design of an ORC which recovers the discharged heat by an existing ICE: the integrated system will supply electricity to a small Nepali village, contributing to a little rise of the life standard of a small and poor community.